2003
DOI: 10.1029/2003jd003766
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term half‐hourly measurement of soil CO2 concentration and soil respiration in a temperate deciduous forest

Abstract: We conducted a field experiment in a cool‐temperate deciduous forest to investigate the dynamic behavior of soil CO2 and the vertical distribution of soil respiration. Soil CO2 concentration (C) was measured half‐hourly at four depths for 6 months in 2000 with infrared gas analyzers installed below ground. Using C profiles, soil surface CO2 efflux (F0), CO2 production rates of the topsoil (PA), and CO2 flux from the subsoil to topsoil (FCA) were evaluated half‐hourly by applying Fick's first law. Some remarkab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
135
3
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(150 citation statements)
references
References 38 publications
11
135
3
1
Order By: Relevance
“…Such temporary increases were often observed after a rain event. The temporary increase in CO2 concentration was also observed at other study sites using successive measurements with CO2 sensors installed in soil (e.g., Hirano et al, 2003;Chen et al, 2005;Desutter et al, 2008). The temporal increase also lasted several days in these studies.…”
Section: Short-time Variation In Ground Surface Fluxsupporting
confidence: 50%
See 1 more Smart Citation
“…Such temporary increases were often observed after a rain event. The temporary increase in CO2 concentration was also observed at other study sites using successive measurements with CO2 sensors installed in soil (e.g., Hirano et al, 2003;Chen et al, 2005;Desutter et al, 2008). The temporal increase also lasted several days in these studies.…”
Section: Short-time Variation In Ground Surface Fluxsupporting
confidence: 50%
“…Some studies have measured soil CO2 concentrations (e.g., van Bochove et al, 2001;Hirano et al, 2003;Chen et al, 2005;Maljanen et al, 2007;DeSutter et al, 2008;Muhr et al, 2009;Liang et al, 2010). These studies revealed seasonal variations in CO2 concentrations; the CO2 concentrations peaked in summer and had been increasing during the snow-covered period, which suggests that the stored CO2 in the soil during the winter might be released to the atmosphere after the Full Paper J.…”
Section: Introductionmentioning
confidence: 99%
“…Davidson et al (1998) predicted that Q 10 values would increase with temperature measurement depth, and recognized that this complicates comparisons between studies. Recently, several field studies with multiple temperature measurement depths have been published (Xu and Qi, 2001;Hirano et al, 2003;Tang et al, 2003;Gaumont-Guay et al, 2006;Khomik et al, 2006;Shi et al, 2006;Wang et al, 2006;Pavelka et al, 2007). All of them show an increase of apparent Q 10 with depth.…”
Section: Introductionmentioning
confidence: 99%
“…The second method to measure soil respiration involves automated soil CO 2 concentration profiles using gas wells (Hirsch et al 2004;Risk et al 2002a) or solid state CO 2 sensors (Hirano et al 2003). With soil CO 2 concentrations profiles, the location of production of CO 2 within the soil profile can be determined (Hashimoto and Komatsu 2006;Risk et al 2002b), but the calculation of soil respiration is dependent on the proper estimate of multiple physical factors such as: (1) variation in soil water content that change CO 2 diffusivity in the soil (Šimůnek and Suarez 1993); and (2) the proper estimation of tortuosity, soil texture, bulk density and porosity which are difficult to determine in rocky soils or water saturated soils (Jassal et al 2005;Pumpanen et al 2008;Turcu et al 2005).…”
Section: Continuous Measurements Of Soil Respirationmentioning
confidence: 99%